Oral piercing - a form of body art or a danger to human health? A literature review - Brzoza, Martyna; Stawińska-Dudek, Julia; Aboud, Ali; Bielecka, Aleksandra; Dubniański, Bartosz (Journal of Education, Health and Sport, 2024)
Introduction and purpose Over the years piercing has become popular as a form of art and self-expression that may concern various areas of the body. However, it may pose significant risks to health. This literature review aims to provide insight into the matter of oral piercing and to examine recent studies investigating the implications of oral piercing on health. It emphasizes the necessity of promoting education regarding this matter and points out the most significant preventive measures such as regular dental examinations and maintaining proper hygiene that should be taken to minimize the negative consequences of oral piercing on health. The state of knowledge According to the examined studies investigating the implications of oral piercing on health, a wide range of complications have been reported. Gingival recession, damage to dentition and gingivitis should be mentioned among the most frequently discussed. Moreover, studies have demonstrated a correlation between the severity of complications and the location of the piercing, specifying the adverse effects of the piercing within lip and tongue areas in particular. They have also underscored the impact of prolongated wear time on the risk of complications, indicating the elevated risk associated with extended periods of wear time. Conclusions To minimize adverse effects of oral piercing on health, it is crucial to underscore the role of proper education in this field and the importance of taking preventive measures such as performing the piercing procedure by well qualified professionals who endure sterile work conditions and maintaining proper aftercare of the ornament. The role of regular dental examinations taken in order to detect and treat potential complications at early stages is also vital.